The Effect of Hiring Top Workers on Productivity: What is the Role of Absorptive Capacity? - Magnus Lodefalk; Aili Tang (Örebro University School of Business, 2017)
We examine heterogeneous productivity effects of hiring top workers on small and medium-sized enterprises, using longitudinal employer-employee data. We find the productivity effect to be stronger for firms with higher absorptive capacity in terms of having a well-educated workforce, being in a knowledge-intensive industry or performing R&D. Technological laggards within an industry benefit more strongly from hiring top workers if their workforce is more well-educated.
Keywords: D22; D24; D83; J24; J62; 330; recruitment; knowledge spillover; firm growth; productivity; SME; absorptive capacity